The Correlation Between Social Support And Incidence Of Depression In Coronary Heart Disease Patients - Pusparany, Rissa Yuniarta; Hartoyo, Mugi; Trisnaningtyas, Wenny; Sudiarto, Sudiarto (RSUP Dr. Kariadi, 2026)
BACKGROUND: Coronary heart disease can cause psychological impacts in the form of depression which, if not managed optimally, can worsen the patient's condition. One of the psychosocial factors that cause depression is low social support. Social support can strengthen individual coping with the acceptance of disease conditions in patients. AIMS: This study aims to determine the relationship between social support and depression in coronary heart disease patients at the Heart Installation of Dr. Kariadi Hospital Semarang. METHODS: This research is a descriptive quantitative correlation with a cross sectional approach. The research sample amounted to 39 respondents calculated by the Isaac and Michael formula with the sampling technique using accidental sampling. The research instruments used were Multidimensional Scale of Perceived Social Support (MSPSS) to assess social support and Beck Depression Inventory-II (BDI-II) to assess depression. RESULTS: The results of the Pearson Product Moment test showed a highly significant correlation between social support and depression (p = 0.000) with a value of r = -0.756 indicating a strong level of correlation with a negative correlation direction. CONCLUSION: The correlation between the two variables is strong and inversely proportional where the higher the social support received, the more depressive symptoms experienced will decrease. Family education is needed to maintain and increase social support to prevent and reduce depression in coronary heart disease patients.